1980
DOI: 10.1111/j.1365-2621.1980.tb07475.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Low‐salt Soluble Protein Patterns of Bovine Muscles Cooked at Different Temperatures, by Sodium Dodecyl Sulfate‐polyacrylamide Gel Electrophoresis

Abstract: Muscle samples from bovine animals were cooked for 10 min from 60-90°C with intervals of about 2°C. Samples were homogenized and centrifuged and the low-salt soluble proteins were obtained thereafter. Photodensitometry was used for the quantitation of proteins on SDS polyacrylamide gels with the enzyme enolase as an internal standard. It was found that a linear relationship existed between peak areas and the enolase concentration up to 60 pg. Enolase was found to be a useful internal standard yielding narrower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…When the sarcoplasmic proteins were extracted from beef by distilled water, followed by heating at 100 ЊC for 3 h, approximately 90% of them became insoluble (Tajima and others 1989). In addition, Caldironi and Bazan (1980) have demonstrated that 80% of low-salt-soluble proteins of bovine muscle were changed to insoluble 1s after heating at 80 ЊC for 1 h. Okayama and others (1991) have also reported a similar result, as described above. These results support the idea that almost all of the sarcoplasmic proteins extracted from meat cubes into water during soaking move to scum during heating.…”
Section: Change Of Proteins In Soup Stock and Scumsupporting
confidence: 63%
“…When the sarcoplasmic proteins were extracted from beef by distilled water, followed by heating at 100 ЊC for 3 h, approximately 90% of them became insoluble (Tajima and others 1989). In addition, Caldironi and Bazan (1980) have demonstrated that 80% of low-salt-soluble proteins of bovine muscle were changed to insoluble 1s after heating at 80 ЊC for 1 h. Okayama and others (1991) have also reported a similar result, as described above. These results support the idea that almost all of the sarcoplasmic proteins extracted from meat cubes into water during soaking move to scum during heating.…”
Section: Change Of Proteins In Soup Stock and Scumsupporting
confidence: 63%
“…243 In addition, Mahoney, et al 244 reported that the increased meltability of cheese products was related to decreased protein molecular size.…”
Section: Molecular Size Modificationmentioning
confidence: 98%
“…The differential insolubilization of sarcoplasmic proteins with heat has been noted by a number of researchers using starch gel electrophoresis (Lee and Grau, 1966) or SDS-PAGE techniques (Lee et al, 1974;Caldironi and Bazan (1980) noted that five sarcoplasmic proteins from beef muscle other than myoglobin were noticeable in SDS-PAGE after heating to 68°C. According to these authors, two proteins had an apparent molecular weight in SDS-PAGE of 40,000 and 55,000.…”
Section: Results and Discussion Total Protein Insolubilizationmentioning
confidence: 96%
“…Protein nitrogen determination (Paul et al, 1966;Roberts and Lawrie, 1974), biuret protein measurements (Davis and Anderson, 1983), differential scanning calorimetry (Wright et al, 1977) and size exclusion high performance liquid chromatography (HPLC) (Davis and Anderson, 1984) have been used to monitor insolubilization of total protein in heated beef, pork, and rabbit muscle. Starch gel electrophoresis (Lee and Grau, 1966), polyacrylamide gel electrophoresis (Laakkonen et al, 1970;Crespo and Ockerman, 1977), and polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS-PAGE) (Lee et al, 1974;Caldironi and Bazan, 1980) have demonstrated that water soluble components of beef, pork and chicken muscle lose solubility differentially with heating.…”
Section: Introductionmentioning
confidence: 99%